Prevalence of female sexual dysfunction and its associated factors among type 2 diabetes mellitus patients in Kuantan, Pahang - Tan, Kui Foung (Kuantan, Pahang : Kulliyyah of Medicine, International Islamic University Malaysia, 2022, 2024)
Impaired sexual function in men is a well-recognized complication of diabetes mellitus. In contrast, sexual dysfunction is relatively less well studied among women. Information related to FSD in Malaysia remains scarce, especially among Type 2 diabetes mellitus (T2DM) patients. The purpose of the study is to assess the prevalence of female sexual dysfunction and its associated factors among T2DM patients attending primary health clinics in Kuantan Pahang. This cross-sectional study was conducted among 241 T2DM patients attending five health clinics in Kuantan. The inclusion criteria were married female who aged 18 to 65 and understand Malay. The exclusion criteria were patients with known case of psychiatric disorder, pregnant women, or those within 6 weeks postpartum and sexual inactive women. Interviewer-administered validated Malay version of Female Sexual Function Index (MVFSFI) was used to screen for FSD. The Malay version of Patient Health Questionnaire-9 (PHQ-9) was used to screen for depression. The statistical analyses were done using Mann-Whitney U test and chi-squared test, and then preceded with binary logistic regression. The median age of respondents involved was 52.9 (7.75). The majority were Malay (79.3%), Muslim (80.5%), housewives (68%), and menopause (54.4%). The prevalence of FSD was 39.8%. The most common sexual dysfunction was desire (63.5%), followed by arousal (44.4%), lubrication (35.7%), orgasm (32.8%), satisfaction (38.6%) and pain (33.6%). Multivariate analysis showed that non-Malay (AOR: 2.5, 95% CI: 1.24 to 5.23), depression (AOR: 4.5, CI: 1.30 to 15.57), and longer duration of marriage (AOR 1.08, CI: 1.03 to 1.14) were significantly associated with FSD while having more children is a protective factor (AOR: 0.82, CI: 0.69 to 0.97). This study shows that nearly 40 percent of T2DM female patients in primary health clinics had FSD. The clinicians should concern sexual health as an essential aspect to be focused on when treating T2DM patients, especially among non-Malay, patients with a longer duration of the marriage, a lesser number of children, and those who presented with depressive symptoms.